Influence of spacing and foliar application of boron and calcium on fruit quality of bitter gourd (Momordica charantia) grown under protected structures - SINGH, ABHAY VIKRAM; SINGH, AWANI KUMAR; JAT, GOGRAJ SINGH; BEHERA, TUSAR KANTI (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted to examine the effect of spacing and foliar application of boron and calcium on fruit quality of bitter gourd grown in nethouse and polyhouse. The variety Pusa Rasdar was found superior for fruit juice (71.43 ml/500 g), DPPH (73.02 mg), chlorophyll (5.34 mg), vitamin C (74.78 mg) and carotenoid content (66.83 mg) per 100 g of fresh fruit weight under nethouse. Most of the quality traits were superior under nethouse grown crop except fruits pulp content. Application of boron @0.2% and calcium @0.6% in combination enhanced fruit juice content (61.80 and 60.83 mL/500 g), DPPH (53.67 and 54.48 mg/100 g), chlorophyll (6.07 and 6.24 mg/100 g), vitamin C (70.14 and 70.09 mg/100 g) and carotenoids (36.13 and 36.96 mg/100 g) under nethouse condition, respectively. High dose of boron (0.4%) and low dose of calcium (0.3%) enhanced fruit pulp content (54.31 and 54.89 g/100 g), respectively, under polyhouse condition. Among the three different spacing, wider spacing (30 cm × 50 cm) increased fruit juice content, DPPH, chlorophyll and carotenoids under nethouse and polyhouse conditions. Closer spacing (20 cm × 50 cm) increased fruit pulp and vitamin C under nethouse and polyhouse conditions. Therefore, growing of bitter gourd crop particularly cv. Pusa Rasdar and Selection-32 under polyhouse and nethouse condition is a cost effective and sustainable strategy to fetch higher price in the market.